Morphotactics basque auxiliaries and the structure of spellout - Arregi, Karlos (Studies in Natural Language and Linguistic Theory, 2012)
This comprehensive treatment of several phenomena in Distributed Morphology explores a number of topics of high relevance to current linguistic theory. It examines the structure of the syntactic and postsyntactic components of word formation, and the role of hierarchical, featural, and linear restrictions within the auxiliary systems of several varieties of Basque. The postsyntactic component is modeled as a highly articulated system that accounts for what is shared and what exhibits variation across Basque dialects. The emphasis is on a principled ordering of postsyntactic operations based on their intrinsic properties, and on the relationship between representations in the Spellout component of grammar with other grammatical modules. The analyses in the book treat related phenomena in other languages and thereby have much to offer for a general morphology readership, as well as those interested in the syntax-morphology interface, the theory of Distributed Morphology, and Basque.